Ethnic residential segregation and identificational assimilation: An intergenerational analysis of those claiming single (heritage) and dual (with Australian) ancestries. (December 2020) - Forrest, James; Johnston, Ron; Siciliano, Frank
Faced with increasing flows of immigrants from countries with very different ethnic and cultural compositions, identity has become an important part of the public debate on immigration and minority ethnic group assimilation. Yet, identificational assimilation, associated with the emergence of a new social identity as ethnic immigrant groups merge with host society members while often retaining some 'inner layer' of heritage ancestry or background, is among the least studied of assimilation sub-processes. Like other aspects of assimilation, it is an intergenerational process, but one which occurs unevenly among immigrant groups from different cultural backgrounds. Spatially, there is an underlying assumption that those more identificationally assimilated will be less segregated from host society members. Focusing on ancestral identification, whether heritage (ethnic or cultural background) only or dual (heritage-Australian), we analyse three generations of a cross-section of ethnic immigrant groups in Sydney, Australia's largest immigrant-receiving city. Results highlight a major identificational shift in the third generation plus the ways in which intergenerational identificational assimilation, though seemingly inexorable, progresses unevenly among ethnic immigrant groups, with results affecting their spatial assimilation.